Exploring the impact of emotional intelligence on portfolio performance: An international exploratory study. Issue 4 (14th November 2016) - El-Chaarani, Hani
Abstract : Purpose: The main purpose of this research is to empirically test the impacts of emotional intelligence score and emotional intelligence processing on the performance of investor's portfolio. Design/methodology/approach: A mail questionnaire survey was conducted on a sample of 983 international investors. The total number of usable responses received was 197 giving a response rate of 20.4 per cent. From 197 investors, 46 accepted to complete the experiment study during two trading hours for each investor from January first until February 19, 2015. Findings: The results reveal a positive impact of emotional intelligence on portfolio performance. Additional analysis shows that the emotional intelligence process has a significant impact on the portfolio performance. The higher impact is revealed when the investors understand the markets tendency, manage their own emotions, take their financial decisions and finally control their personnel emotions during market fluctuations. The lower impact is detected when investors take reactive decisions after perceiving the markets tendency. This research also reveals that the investors have high capacity to manage and control their emotions during market fluctuations especially who are characterized by high emotional intelligence level. Research limitations/implications: The first limit of this research is the exploration of limited number of investors and financial operations during limited period. Therefore, the results could not be generalized, and further studies should include larger samples during larger period. The second limitation concerns the used variables to measure the portfolio performance and the emotional intelligence level. For future studies, it will be preferred to use other quantitative and qualitative variables lead to measure the different analytical dimensions of portfolio performance and emotional intelligence. Practical implications: The results hold implications for investors that seek to enhance efficiently and effectively the portfolio performance. It also prompts investors to focus on effort that can improve the management and the control of personnel emotions. Originality/value: This paper presents one of the first empirical studies that attempt to explore how emotional intelligence and, particularly, emotional process serve to sustain the performance of portfolio during market fluctuations.